2012
DOI: 10.1038/ejhg.2012.207
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein receptor mutations generate synthetic genome-wide associations

Abstract: Genome-wide association (GWA) studies have discovered multiple common genetic risk variants related to common diseases. It has been proposed that a number of these signals of common polymorphisms are based on synthetic associations that are generated by rare causative variants. We investigated if mutations in the low-density lipoprotein receptor (LDLR) gene causing familial hypercholesterolemia (FH, OMIM #143890) produce such signals. We genotyped 480 254 polymorphisms in 464 FH patients and in 5945 subjects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…D′ = 0.95 and 0.96, respectively, with rs4905179) and generally with many common variants in this locus (Figure 4), suggesting little genetic recombination. This proof-of-principle approach, revealing that signals of common variants in fact merely reflect rarer variants, has recently also been shown for some of the loci regulating low-density lipoprotein (LDL) cholesterol [31], [32]. Yet for other loci linked to LDL cholesterol, as well as for loci influencing other traits, both common and low-frequent variants contributed independently of the original GWAS signal to the phenotypic trait [31], [33], [34].…”
Section: Discussionmentioning
confidence: 89%
“…D′ = 0.95 and 0.96, respectively, with rs4905179) and generally with many common variants in this locus (Figure 4), suggesting little genetic recombination. This proof-of-principle approach, revealing that signals of common variants in fact merely reflect rarer variants, has recently also been shown for some of the loci regulating low-density lipoprotein (LDL) cholesterol [31], [32]. Yet for other loci linked to LDL cholesterol, as well as for loci influencing other traits, both common and low-frequent variants contributed independently of the original GWAS signal to the phenotypic trait [31], [33], [34].…”
Section: Discussionmentioning
confidence: 89%
“…Empirical studies, involving resequencing of GWAS loci, have now found several instances where GWAS signals for various disorders or traits can be partially or largely attributed to effects of rare variants at the associated locus (Oosterveer et al, 2013;Sanna et al, 2011;Saunders et al, 2014;Thun et al, 2013). This effect has not been seen in all cases, however (Hunt et al, 2013).…”
Section: Common Variants -Genome--wide Association Studiesmentioning
confidence: 99%
“…Several common variant association studies (CVASs) formerly called genome‐wide association studies (GWASs), resequencing and targeted approaches have revealed a wealth of information on the genetic basis for dyslipidemia, and several predisposing genes identified thus far have been implicated in hypercholesterolemia , hypertriglyceridemia or low HDL‐cholesterol levels . Despite the volume of these data on dyslipidemia‐related genes, only a fraction of the heritability of the disease traits has been explained thus far, and the predisposing gene variants, particularly for LHDLC, are far from being completely unraveled .…”
mentioning
confidence: 99%